ISLAMIC EDUCATION AND ENGLISH LANGUAGE ACQUISITION IN EARLY CHILDHOOD: CHALLENGES AND OPPORTUNITIES - Rafi’i, Muhammad (Proceeding International Seminar of Islamic Studies, 2025)
This study explores the intersection of early childhood English language acquisition and Islamic education, focusing on both the challenges and opportunities in this context. The increasing need for English proficiency in Islamic learning environments is driven by globalization. Key obstacles include cultural perceptions, limited teacher competence, and inadequate resources. Despite these challenges, the study highlights the potential to integrate Islamic values into English instruction, enhancing engagement and relevance for young learners. Using qualitative methods such as interviews and classroom observations, the study finds that with culturally responsive and innovative teaching strategies, children in Islamic educational settings can significantly improve their English skills. This research contributes to the broader discourse on multilingual education and offers practical insights for educators and policymakers aiming to create inclusive and effective learning environments aligned with both Islamic principles and modern language pedagogy.